Management of the Wound in Type IIIB Open Tibiofibular Fractures: The Role of Improvised Vacuum‑assisted Closure Dressing - Babalola, O. M.; Salawu, Oni Nasiru; Ahmed, B. A.; Ibraheem, G. H.; Mejabi, J. O. (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: The negative pressure used in vacuum‑assisted closure (VAC) dressing helps to suck out fluid and bacteria from the wound and enhances granulation tissue formation and wound contraction, thus causing wound healing. Aim: The aim of the study is to demonstrate the effectiveness of VAC in extensive wound management when using local materials. Methods: This was a prospective study in which all consented patients who met the inclusion criteria within the study period were included in the study; suctioning machine, rubber tube, foam and cling film were adapted to make the local VAC which was used to manage the wound. The results were analysed by IBM SPSS Version 22. Results: Thirty‑two wounds were managed with VAC, there were 28 males and four females, the mean age of patients was 33.7 ± 9.6 years, the mean length of wound managed was 10.6 ± 2.9 cm and the average number of dressing was five times. All wounds were culture positive at the beginning of the management, with Staphylococcus aureus being the most common organism. At the end of VAC treatment, 90.6% of the wound were negative for culture. Healing by secondary wound intension occurred in 50% of the wound, secondary suturing was done in 31.2% of the wound, while 18.8% of the wound had split‑thickness skin grafting. The complications noted during the treatment are pain in 9.3% of the patients and skin excoriation in 3.1% of the patients. Conclusion: VAC method of wound management using local materials is effective in the treatment of extensive wound, and it is associated with less frequent dressing to achieve the desired result.